2015
DOI: 10.1098/rstb.2013.0379
|View full text |Cite
|
Sign up to set email alerts
|

Paging through history: parchment as a reservoir of ancient DNA for next generation sequencing

Abstract: Parchment represents an invaluable cultural reservoir. Retrieving an additional layer of information from these abundant, dated livestock-skins via the use of ancient DNA (aDNA) sequencing has been mooted by a number of researchers. However, prior PCR-based work has indicated that this may be challenged by cross-individual and cross-species contamination, perhaps from the bulk parchment preparation process. Here we apply next generation sequencing to two parchments of seventeenth and eighteenth century norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 44 publications
1
60
0
Order By: Relevance
“…Kirby et al (12) also used destructive sampling techniques to analyze a Koran and other objects. Teasdale et al (13) have recently reported genomic data from postmedieval parchment using, on average, 50 mg of parchment. In addition to the destructive nature of sampling, a further hidden cost of molecular analysis is adequate storage of extracted samples.…”
Section: Species Identification Of Parchmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Kirby et al (12) also used destructive sampling techniques to analyze a Koran and other objects. Teasdale et al (13) have recently reported genomic data from postmedieval parchment using, on average, 50 mg of parchment. In addition to the destructive nature of sampling, a further hidden cost of molecular analysis is adequate storage of extracted samples.…”
Section: Species Identification Of Parchmentmentioning
confidence: 99%
“…A notable proponent of follicle pattern analysis was Ryder (10), who used the technique to identify animal species; however, not all parchments had discernible follicle patterns, not every pattern could be identified, and paleographers have often been overconfident in their ability to discern species origin from such patterns. Protein (11,12) and DNA-based methods (13)(14)(15)(16)(17) potentially offer absolute determination of species but, until now, have had other limitations. Toniolo et al (11) analyzed 5 mg of parchment from the 13th-century "Marco Polo Bible" at the Biblioteca Medicea Laurenziana, and used peptide sequences to identify a single leaf as calfskin, although if more leaves had been analyzed the results may have revealed different species as was the case with the family's archival documents (Table S1).…”
Section: Species Identification Of Parchmentmentioning
confidence: 99%
“…The results presented in this article and the research described in literature (Burger et al, 2000;Teasdale et al, 2014) suggest that DNA present in historical parchments can be a good source of information about cultural heritage objects.…”
Section: Discussionmentioning
confidence: 78%
“…This could be attributed to the greater number of copies of mtDNA compared to that of nuclear DNA (nuDNA), as well as shorter product fragments that could facilitate further analyses (Bollongino et al, 2006;Vuissoz et al, 2007;Scheu et al, 2008;Stock et al, 2009;Rizzi et al, 2012). However, it must be emphasized that analyses based on ancient mitochondrial DNA may be more vulnerable to contamination than those involving genomic DNA (Teasdale et al, 2014). The cytochrome b sequence is often used with great success in aDNA analyses (Poulakakis et al, 2007;Campana et al, 2010;Pangallo et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation